Examining desensitization using facial electromyography:Violent videogames, gender, and affective responding. (September 2016) - Read, Glenna L.; Ballard, Mary; Emery, Lisa J.; Bazzini, Doris G.
Abstract: The results of research investigating the effects of violent videogames have been inconsistent. Some evidence suggests that exposure to violent videogames decreases physiological arousal and results in desensitization to subsequent exposure to violent stimuli. Other research does not support these findings. This study examined physiological and affective desensitization to violent videogame play. Participants played a violent or non-violent videogame and then viewed aggressive, pleasant, and neutral images. Participants' negative affect in response to the images was assessed by examining activity in the brow muscle region (i.e., corrugator supercilii ), heart rate (HR), self-reported affect, and self-reported arousal. Based on previous research regarding the General Aggression Model (GAM), we expected that participants who played the violent videogame would demonstrate desensitization as evidenced by less reactivity in the corrugator supercilii region and less HR reactivity in response to violent images than participants who played the nonviolent videogame. We also expected that participants who played the violent videogame would rate the aggressive images as less aversive than those who played the nonviolent game. Contrary to our expectations, the findings were not consistent with the hypotheses based on the GAM. Highlights: Examined physiological and affective desensitization to one violent videogame. Participants played a (non)violent videogame then looked at aggressive images. Examined physiological and affective desensitization to one violent video game. Participants did not differ in self-reported affect or arousal. The violent, compared to the nonviolent, videogame did not produce desensitization.